New Cartridge Design for Assault Rifle - Peter LISÝ (Wojskowa Akademia Techniczna, 2020)
The article deals with the possible design of a new cartridge for an automatic assault rifle. This hypothetical design is based on the analysis of five automatic assault rifle cartridges which are currently used in armies: 7.62 × 51 mm NATO, 7.62 × 39 mm M 43, 5.56 × 45 mm NATO and also another two cartridges which are under testing both 6.8 × 43 mm Rem. SPC and 6.5 × 38 mm Grendel. The analysis of a new cartridge including internal ballistics, external ballistics, and terminal ballistics energy disposed to the target upon an impact is introduced in the article. The goal was to create a cartridge that would have better ballistic performance than 5.56 × 45 mm NATO and it would still possess enough accuracy of fire and speed, so that it could dispose at least minimal kinetic energy necessary to incapacitate individuals. Also it is important to maintain the constancy of this effect for the long distance shooting, somewhere around 500 m, during battles in an open area (effective range of 5.56 × 45 mm automatic assault rifles is normally of about 300 m what only suffices in close quarter battles). To achieve it, the bullet must have the higher sectional density than the 5.56 × 45 mm cartridge. The sectional density reflects the capability of bullet to penetrate through the human tissue within the requirements of wound ballistics. Based on the analysis, the value of sectional density should be approximately of 0.21 g/mm2. The function of fully automatic firing depends on the size of the recoil energy of a weapon which is also related to the muzzle energy that cannot surpass the amount of 2500 J. The new cartridge design is based on the 6 mm Scenar bullet (FMJ – Full Metal Jacket bullet with a weight of 5.8 g) made by the Lapua Company. All the ballistic parameters must be within the intervals of strength and construction possibilities of small arms ammunition. To create a possible variation of the mentioned cartridge where its bullet will be powered by a nitrocellulose propellant (originally made in Czech Republic), a new cartridge case will be created.
Keywords: Amunicja strzelecka